Sustainability Principles of Arabic Language Curriculum Design: Contextual and Cultural, Flexibility Principles, Evaluation and Feedback Principles - Nurkhalish Rahmat; Isop Syafei (UIN Sunan Gunung Djati Bandung, 2025)
The Arabic language curriculum plays a crucial role in building a well-planned and relevant learning process. An effective curriculum design must be based on fundamental principles that support the success of learning, including relevance, integration, balance, flexibility, and sustainability. The principle of relevance highlights the need for a curriculum that aligns with students' needs and their social contexts, whether in religious, educational, or career aspects. Integration requires the combination of language skills and linguistic components, while balance ensures the appropriate proportion between theory and practice. Flexibility allows the curriculum to adapt to changing times and the diverse characteristics of students. The principle of sustainability demands that the curriculum be adaptive, proactive, and visionary, in line with social development, technological advancement, and the ongoing process of globalization. Therefore, sustainability is essential in the development of the Arabic language curriculum and in creating an educational system that is both enduring and competitive in the 21st century.